Recent advances in lipid nanovesicles for targeted treatment of spinal cord injury - Lu, Di; Wu, Jiu-Ping; Yang, Qi-Wei; Wang, Hua-Yi; Yang, Jun-Jie; Zhang, Gang-Gang; Wang, Chen; Yang, Yan-Lian; Zhu, Ling; Sun, Xin-Zhi (Frontiers in Bioengineering and Biotechnology, 2023)
The effective regeneration and functional restoration of damaged spinal cord tissue have been a longstanding concern in regenerative medicine. Treatment of spinal cord injury (SCI) is challenging due to the obstruction of the blood-spinal cord barrier (BSCB), the lack of targeting of drugs, and the complex pathophysiology of injury sites. Lipid nanovesicles, including cell-derived nanovesicles and synthetic lipid nanovesicles, are highly biocompatible and can penetrate BSCB, and are therefore effective delivery systems for targeted treatment of SCI. We summarize the progress of lipid nanovesicles for the targeted treatment of SCI, discuss their advantages and challenges, and provide a perspective on the application of lipid nanovesicles for SCI treatment. Although most of the lipid nanovesicle-based therapy of SCI is still in preclinical studies, this low immunogenicity, low toxicity, and highly engineerable nanovesicles will hold great promise for future spinal cord injury treatments.